Application of hierarchical method and fuzzy AHP-TOPSIS method for multi-criteria decision making in financing - Elham Soleimani; Mohaddeseh Dehyadegari; Hassan Zarei Gerami (goodwood publishing)
Purpose: One way to make more profit in different companies is to choose the right method of financing. While the impact of financial structure on the economic structure is so important that today they believe that economic growth cannot be achieved without an efficient financial sector. The method of financing is financial. At first, in this study, the fuzzy Delphi method (Delphi) has been used in order to identify the factors and criteria of supply. Research methodology: The absorption of foreign capital has been identified as a method of financing. For this purpose, in this research, AHP hierarchical analysis method is used. Results: In this article, the application of fuzzy AHP - TOPSIS method for the problem of financing is investigated. The process of managing financial resources is one of the reasons for allocating its technical equipment to various applications in this company. Limitations: However, the results of our studies show that although a set of known values in this company, the financing process may not adhere strongly to these values. Emphasis on evaluation aspects - changes in various areas that indicate local values may also affect the supply trend. Contribution: Multi-criteria decision methods are useful in that they provide a basis for analyzing and transforming complex and complex problems into simpler ones; In that framework, the planner can easily evaluate the options with the help of criteria and sub-criteria. Using these methods can help a lot in choosing the best available solution. Other advantages of these methods include flexibility, simplicity of calculations and the possibility of the final ranking of options.